Synthesis and structural evolution of Pt nanotubular skeletons: revealing the source of the instability of nanostructured electrocatalysts1. Issue 24 (28th June 2015) - Wang, Rongyue; Higgins, Drew C.; Prabhudev, Sagar; Lee, Dong Un; Choi, Ja-Yeon; Hoque, Md Ariful; Botton, Gianluigi A.; Chen, Zhongwei
<x xml:space="preserve">Abstract</x> Grain boundaries are revealed to be a primary source of one-dimensional Pt nanostructure instability by comparing the structural evolution processes of rationally synthesized tubular structures with Pt/C.